МЕТОДИ СПОСТЕРЕЖЕННЯ НАД МОВНИМИ ЯВИЩАМИ В НАВЧАННІ ФОНЕТИКИ НА ПРОФІЛЬНОМУ РІВНІ (Педагогіка вищої та середньої школи, 2008)
The article investigates the problem of using the observation method in learning linguistic phenomena on the professionally orientated level of teaching the Ukrainian phonetics.